Chemical features and antioxidant profile by Schizophyllum commune produced on different agroindustrial wastes and byproducts of biodiesel production. (1st November 2020) - Basso, Vanessa; Schiavenin, Claudiane; Mendonça, Simone; de Siqueira, Félix Gonçalves; Salvador, Mirian; Camassola, Marli
Highlights: S. commune showed the highest productivity in a substrate rich in lignin. S. commune showed a high content (59.61%) of dietary fibre. Substrates with low mushroom yield led to an increase in their phenolic content. Macrofungi phenolic content showed a positive correlation with antioxidant activity. Abstract: Schizophyllum commune VE_07 was produced in different culture media containing pine sawdust (PS), grape residue (GR), cotton cake (CC) and jatropha seed cake (JC). The content of phenolics and antioxidant activity were determined for the substrates and mushrooms produced. The content of ß-glucans and the composition of S. commune were also evaluated. The medium formulated with 94% grape residue enabled the highest values of yield, biological efficiency, and productivity. Mushrooms grown in this condition showed the highest value (13.14%) of ß-glucans. The contents of proteins and dietary fibre were 16.59% and 59.61%, respectively. Mushrooms grown in cotton cake showed the highest phenolic content (291.51 ± 1.83 mg GAE/ 100 g mushroom) and antioxidant activity (58.15 ± 0.86 DPPH % scavenging). The results obtained indicate that substrate composition affected the production of S. commune and its chemical composition.